2003
DOI: 10.1038/sj.ijo.0802295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive dietetic interventions on weight and glycaemic control in overweight men with Type II diabetes: a randomised trial

Abstract: OBJECTIVE:To investigate the effectiveness of intensive innovative methods for implementing dietary prescriptions on weight management and glycaemic control in overweight men with Type II diabetes. DESIGN: A randomised clinical trial with a 12-week intervention period F three isocaloric dietary intervention groups (intermittent energy restriction, pre-portioned meals and self-selected meals) each with weekly dietitian contact F and a followup visit after 18 months. SUBJECTS: A total of 51 men with Type II diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 22 publications
7
121
2
Order By: Relevance
“…In contrast to our results and others [17], similar trials performed in non-diabetic, obese individuals have reported long-term weight loss principally due to reductions in fat mass [21,22]. This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In contrast to our results and others [17], similar trials performed in non-diabetic, obese individuals have reported long-term weight loss principally due to reductions in fat mass [21,22]. This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23].…”
Section: Discussioncontrasting
confidence: 95%
“…The amount of weight lost after the initial energy restriction period was comparable to previous studies over 10 to 12 weeks in patients with Type 2 diabetes [17,18]. Consistent with other studies, both groups regained weight during follow-up, but maintained a net weight loss at Week 64 [6,19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…27 Other studies have indicated that the effects of lifestyle interventions are often modest. 7,9 A randomised trial, which assigned 423 overweight people to a structured commercial weight loss programme or self-help programme, observed mean (7s.d.)…”
Section: Discussionmentioning
confidence: 99%
“…However,in previous studies, it was observed that a strict calorie restriction, as performed in the first weeks after bariatric surgery, could bring itself to a normalization of plasma glucose and insulin levels before body weight decrease [19,20].…”
Section: Physiopathology Of Metabolic Improvement After Metabolic Surmentioning
confidence: 96%